The Effect of Content Marketing, Celebrity Endorsers and Testimonials on Consumer Brand Awareness at Eighteen Coffee Sukajadi - Bianti F. F. Mooduto; Tetty Herawaty; Ratih Purbasari (Eduvest - Journal of Universal Studies, 2025)
This research aims to measure the influence of Content Marketing, Celebrity Endorser and Testimonials on Consumer Brand Awareness at Eighteen Coffee Sukajadi. In general, the influence of content marketing, celebrity endorsements and testimonials on consumer brand awareness can vary depending on various factors, such as consumer tastes and preferences. By using quantitative methods and a survey approach, the results of this research show that the influence of Content Marketing, Celebrity Endorser and Testimonials on Consumer Brand Awareness at Eighteen Coffee Sukajadi is not very significant because only the testimonial variable has a positive value, while Content Marketing and Celebrity Endorser have a negative value. This then emphasizes that the role of Testimonials in the current digital era is still quite influential. Even though the trend in marketing strategies continues to develop towards more advanced ones, such as Content Marketing and Celebrity Endorser, in fact, testimonials that are considered simpler actually have more influence.